Corporate Social Responsibility (CSR) and Cost of Capital: Evidence from the Indonesian Capital Market - Yanti Budiasih; Rafiullah Amin; Shazia Akhtar (Yayasan Adra Karima Hubbi, 2025)
Corporate Social Responsibility (CSR) has become a critical component of corporate strategy, with growing evidence suggesting its impact on financial performance and cost of capital. In Indonesia, where sustainable business practices are increasingly prioritized, understanding the relationship between CSR and cost of capital is essential for both firms and investors. This study examines the influence of CSR activities on the cost of capital for firms listed on the Indonesian Stock Exchange, focusing on how CSR initiatives affect investor perceptions and risk assessments. The research aims to provide empirical evidence on whether CSR can serve as a strategic tool to reduce the cost of capital and enhance firm value. Using a quantitative approach, this study analyzes financial data and CSR disclosures from 150 firms listed on the Indonesian Stock Exchange over a five-year period. Regression analysis is employed to assess the relationship between CSR performance and cost of capital, measured by weighted average cost of capital (WACC). The findings reveal that firms with higher CSR performance tend to have a lower cost of capital, indicating that CSR initiatives can reduce perceived risk and attract socially responsible investors. The study concludes that CSR activities positively influence the cost of capital, providing firms with a financial incentive to invest in sustainable practices. This research contributes to the discourse on CSR and corporate finance by offering practical insights for firms seeking to enhance their financial performance through responsible business practices.